2004
DOI: 10.1002/neu.10346
|View full text |Cite
|
Sign up to set email alerts
|

Multiple roles of ephrins during the formation of thalamocortical projections: Maps and more

Abstract: The functional architecture of the cerebral cortex is based on intrinsic connections that precisely link neurons from distinct cortical laminae as well as layer-specific afferent and efferent projections. Experimental strategies using in vitro assays originally developed by Friedrich Bonhoeffer have suggested that positional cues confined to individual layers regulate the assembly of local cortical circuits and the formation of thalamocortical projections. One of these wiring molecules is ephrinA5, a ligand fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 80 publications
(55 reference statements)
2
50
0
Order By: Relevance
“…We found a particularly strong signal at E16.5 in the primitive primary somatosensory cortex (S1), when thalamic axons reach the subplate zone. This is consistent with the presence of ephrinA5 mRNA in the subplate and cortical plate of S1 at this stage [22-24,27]. Indeed, ephrinA5 is thought to interact with and repulse ventrobasal thalamic terminal arbors expressing EphA4, and to be responsible for the precise topographic mapping of thalamic afferents into S1 [24].…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…We found a particularly strong signal at E16.5 in the primitive primary somatosensory cortex (S1), when thalamic axons reach the subplate zone. This is consistent with the presence of ephrinA5 mRNA in the subplate and cortical plate of S1 at this stage [22-24,27]. Indeed, ephrinA5 is thought to interact with and repulse ventrobasal thalamic terminal arbors expressing EphA4, and to be responsible for the precise topographic mapping of thalamic afferents into S1 [24].…”
Section: Discussionsupporting
confidence: 72%
“…Previous studies showed different patterns of ephrinA5 mRNA expression, depending of the thalamic nuclei and the stage observed: at E13.5, Bolz et al [27] described a weak mRNA expression in the ventricular zone of the dorsal thalamus at the caudal level with no detectable expression in the mid- or rostral levels of the dorsal thalamus. Feldheim et al [10] described ephrinA5 mRNA expression from E14.5, in the dorsal and ventral lateral geniculate nuclei in a ventral, lateral and anterior (high) to dorsal, medial and posterior (low) gradient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A majority of earlier studies focused on the role of ephrinA5 in developmental biology, especially the nervous system (Bolz et al, 2004;Otal et al, 2006). Recently, the role of ephrinA5 in cancer has gained attention, and the expression pattern of ephrinA5 has been examined in several types of cancers, such as ovarian cancer (Herath et al, 2006) and osteosarcoma (Varelias et al, 2002).…”
Section: Discussionmentioning
confidence: 99%